1999
DOI: 10.1080/106351599259997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for the Compilospecies Model of Reticulate Evolution in Armeria (Plumbaginaceae)

Abstract: Cladistic analyses of the nuclear ribosomal DNA (nrDNA) internal transcribed spacer (ITS) sequences from 55 samples corresponding to 34 taxa in the genus Armeria reveal that ITS sequence diversity among and within species utterly conflicts with patterns of morphological similarity. Three facts are apparent from the results here reported: (1) different samples of a single subspecies, A. villosa subsp. longiaristata, appear in three of the five major clades; (2) samples of at least one of the six subspecies of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 69 publications
4
71
0
2
Order By: Relevance
“…3A). The existence of a geographical structure to the cpDNA data, such that samples show affinity according to geographical area of origin rather than to morphology and thus traditional systematic arrangement, could confuse patterns at morphological and ecological levels (Fuertes Aguilar et al, 1999a;Feliner et al, 2004). Geographical patterning in cpDNA markers has been reported for the Tasmanian eucalypts (McKinnon et al, 2001(McKinnon et al, , 2004, for Iberian species of Phlomis (Albaladejo et al, 2005) and for white oaks in Europe (Dumolin-Lapé-gue et al, 1997;Petit et al, 2002).…”
Section: Fit With Ecology and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). The existence of a geographical structure to the cpDNA data, such that samples show affinity according to geographical area of origin rather than to morphology and thus traditional systematic arrangement, could confuse patterns at morphological and ecological levels (Fuertes Aguilar et al, 1999a;Feliner et al, 2004). Geographical patterning in cpDNA markers has been reported for the Tasmanian eucalypts (McKinnon et al, 2001(McKinnon et al, , 2004, for Iberian species of Phlomis (Albaladejo et al, 2005) and for white oaks in Europe (Dumolin-Lapé-gue et al, 1997;Petit et al, 2002).…”
Section: Fit With Ecology and Distributionmentioning
confidence: 99%
“…Geographical patterning in cpDNA markers has been reported for the Tasmanian eucalypts (McKinnon et al, 2001(McKinnon et al, , 2004, for Iberian species of Phlomis (Albaladejo et al, 2005) and for white oaks in Europe (Dumolin-Lapé-gue et al, 1997;Petit et al, 2002). In these plant groups there is mounting evidence for the presence of several haplotypes within a single species, shared among species within geographical regions, with introgression and hybridisation being invoked as the most likely cause (Dumolin-Lapégue et al, 1997;Steane et al, 1998;Fuertes Aguilar et al, 1999a;Jackson et al, 1999;McKinnon et al, 2001;Petit et al, 2002). Given that the species in the present analysis hybridise in nature (Brock and Brown, 1961;Spies et al, 1992;Visser and Spies, 1994a, b, c, d;Waters, 2007), the occurrence of several ploidy forms within a single species, haplotype sharing among species from the same area (Waters, 2007;Waters et al, 2008) and continuous variation in morphological characters among several species, geographical patterning could offer an explanation to some of the patterns evident in the plastid tree presented here (Fig.…”
Section: Fit With Ecology and Distributionmentioning
confidence: 99%
“…Double-strand amplification of the ITS region (ITS1+5.8s+ITS2) was performed with P1A and P4 primers (Fuertes Aguilar & al., 1999b). The PCR profile for the amplification of the ITS region comprised an initial step of 94ºC (5 min), 38 cycles with 94ºC (30 s), 52ºC (30 s), and 72ºC (60 s) and a final extension step of 72ºC (10 min).…”
Section: Methodsmentioning
confidence: 99%
“…The fact that intraindividual heterogeneity for ITS repeat copies can remain for a given period of time following a hybridization event despite the action of concerted evolution (Zimmer & al., 1980) also makes this marker useful in detecting cases of reticulate evolution among divergent lineages (Sang & al., 1995;Whittall & al., 2000;Fuertes Aguilar & Nieto Feliner, 2003). Even if concerted evolution has been active and different copies are homogenised, ITS sequence data may still provide valuable information on reticulate evolution when showing incongruent patterns with respect to other differently inherited markers (e.g., cpDNA, Rieseberg, 1991) or morphological and biogeographical evidence (Sytsma, 1990;Fuertes Aguilar & al., 1999b;Nieto Feliner & al., 2004). The genus Phlomis L. (Lamiaceae) comprises over Systematic and evolutionary relationships within the diploid Western Mediterranean Phlomis crinita/lychnitis complex remain controversial apparently due to hybridization and introgression.…”
Section: Introductionmentioning
confidence: 99%
“…The main causes for disagreement between gene phylogeny and taxonomy at this level appear to be horizontal transfer and lineage sorting (deep coalescence; Doyle, 1992). Since comparison with plastid DNA trees is relatively unsuccessful in our study, possible cases of horizontal transfer might be suggested based on the detection of additive polymorphic sites (APS; Rauscher & al., 2002;Wichman & al., 2002) and the concurrence of ITS similarity and geographic sympatry (Fuertes Aguilar & al., 1999b).…”
Section: Discussionmentioning
confidence: 99%